Agile and Versatile Quantum Communication: Signatures and Secrets - Richter, Stefan; Thornton, Matthew; Khan, Imran; Scott, Hannah; Jaksch, Kevin; Vogl, Ulrich; Stiller, Birgit; Leuchs, Gerd; Marquardt, Christoph; Korolkova, Natalia (Physical Review X, 2021)
Agile cryptography allows for a resource-efficient swap of a cryptographic core in case the security of an underlying classical cryptographic algorithm becomes compromised. Conversely, versatile cryptography allows the user to switch the cryptographic task without requiring any knowledge of its inner workings. In this paper, we suggest how these related principles can be applied to the field of quantum cryptography by explicitly demonstrating two quantum cryptographic protocols, quantum digital signatures (QDS) and quantum secret sharing (QSS), on the same hardware sender and receiver platform. Crucially, the protocols differ only in their classical postprocessing. The system is also suitable for quantum key distribution (QKD) and is highly compatible with deployed telecommunication infrastructures, since it uses standard quadrature phase-shift keying encoding and heterodyne detection. For the first time, QDS protocols are modified to allow for postselection at the receiver, enhancing protocol performance. The cryptographic primitives QDS and QSS are inherently multipartite, and we prove that they are secure not only when a player internal to the task is dishonest, but also when (external) eavesdropping on the quantum channel is allowed. In our first proof-of-principle demonstration of an agile and versatile quantum communication system, the quantum states are distributed at GHz rates. A 1-bit message may be securely signed using our QDS protocols in less than 0.05 ms over a 2-km fiber link and in less than 0.2 s over a 20-km fiber link. To our knowledge, this also marks the first demonstration of a continuous-variable direct QSS protocol.
CRIS-Team Scopus Importer:2021-03-19

Attacks on practical quantum key distribution systems (and how to prevent them) - Jain, Nitin; Stiller, Birgit; Khan, Imran; Elser, Dominique Alexander; Marquardt, Christoph; Leuchs, Gerd (Contemporary Physics, 2016)
With the emergence of an information society, the idea of protecting sensitive data is steadily gaining importance. Conventional encryption methods may not be sufficient to guarantee data protection in the future. Quantum key distribution (QKD) is an emerging technology that exploits fundamental physical properties to guarantee perfect security in theory. However, it is not easy to ensure in practice that the implementations of QKD systems are exactly in line with the theoretical specifications. Such theory–practice deviations can open loopholes and compromise security. Several such loopholes have been discovered and investigated in the last decade. These activities have motivated the proposal and implementation of appropriate countermeasures, thereby preventing future attacks and enhancing the practical security of QKD. This article introduces the so-called field of quantum hacking by summarising a variety of attacks and their prevention mechanisms.
CRIS-Team Scopus Importer:2021-06-29
Keywords: countermeasures; practical data security; quantum computer; Quantum cryptography; quantum hacking; quantum key distribution

Quantum hacking of continuous-variable quantum key distribution systems: Realtime Trojan-horse attacks - Stiller, Birgit; Khan, Imran; Jain, Nitin; Jouguet, P.; Kunz-Jacques, S.; Diamanti, E.; Marquardt, Christoph; Leuchs, Gerd (Conference on Lasers and Electro-Optics Europe - Technical Digest, 2015)
We experimentally demonstrate successful Trojan-horse attacks on laboratory and commercial continuous-variable quantum key distribution systems with binary and Gaussian modulation. Furthermore, we analyze appropriate countermeasures regarding their spectral performance.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Optical pulses; Optical refraction; Optical variables control; Phase modulation; Protocols; Security

Quantum-limited measurements of optical signals from a geostationary satellite - Günthner, Kevin; Khan, Imran; Elser, Dominique Alexander; Stiller, Birgit; Bayraktar, Ömer; Mueller, Christian R.; Saucke, Karen; Troendle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optica, 2017)
The measurement of quantum signals that travel through long distances is fundamentally and technologically interesting. We present quantum-limited coherent measurements of optical signals that are sent from a satellite in geostationary Earth orbit to an optical ground station. We bound the excess noise that the quantum states could have acquired after having propagated 38,600 km through Earth’s gravitational potential, as well as its turbulent atmosphere. Our results indicate that quantum communication is feasible, in principle, in such a scenario, highlighting the possibility of a global quantum key distribution network for secure communication.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (010.1300) Atmospheric propagation; (060.1660) Coherent communications; (060.2605) Free-space optical communication; (270.5565) Quantum communications; (270.5568) Quantum cryptography

Quantum-limited measurements of optical signals from a satellite in geostationary earth orbit - Günthner, Kevin; Khan, Imran; Elser, Dominique; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Quantum-limited measurements of signals from geostationary earth orbit - Elser, Dominique; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (European Conference on Optical Communication, ECOC, 2016)
Quantum key distribution (QKD) has been implemented in metropolitan area networks around the world. Optical satellite communication is seen as suitable to provide the missing long-haul interconnections. We validate this approach by quantum measurements of optical signals from space.
CRIS-Team Scopus Importer:2021-06-29

Quantum measurements of signals from the Alphasat TDP1 laser communication terminal - Elser, D.; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, K.; Tröndle, D.; Heine, F.; Seel, S.; Greulich, P.; Zech, H.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Quantum optics [1] can be harnessed to implement cryptographic protocols that are verifiably immune against any conceivable attack [2]. Even quantum computers, that will break most current public keys [3, 4], cannot harm quantum encryption. Based on these intriguing quantum features, metropolitan quantum networks have been implemented around the world [5-15]. However, the long-haul link between metropolitan networks is currently missing [16]. Existing fiber infrastructure is not suitable for this purpose since classical telecom repeaters cannot relay quantum states [2]. Therefore, optical satellite-to-ground communication [17-22] lends itself to bridge intercontinental distances for quantum communication [23-40].
CRIS-Team Scopus Importer:2021-06-29

Risk analysis of Trojan-horse attacks on practical quantum key distribution systems - Jain, Nitin; Stiller, Birgit; Khan, Imran; Makarov, Vadim; Marquardt, Christoph; Leuchs, Gerd (IEEE Journal of Selected Topics in Quantum Electronics, 2015)
An eavesdropper Eve may probe a quantum key distribution (QKD) system by sending a bright pulse from the quantum channel into the system and analyzing the back-reflected pulses. Such Trojan-horse attacks can breach the security of the QKD system, if appropriate safeguards are not installed or if they can be fooled by the Eve. We present a risk analysis of such attacks based on extensive spectral measurements, such as transmittance, reflectivity, and detection sensitivity of some critical components used in a typical QKD systems. Our results indicate the existence of wavelength regimes, where the attacker gains considerable advantage as compared to launching an attack at 1550 nm. We also propose countermeasures to reduce the risk of such attacks.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Electrooptic modulators; Fiber optics; Infrared detectors; Infrared spectra; Optical pulses; Optical receivers; Photodetectors; Quantum cryptography; Quantum key distribution; Reflectometry; Supercontinuum; Transmittance; Trojan-horse attack

Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication